Flat nonaqueous battery and method for manufacturing the same

JP2025022035APending Publication Date: 2025-02-14MAXELL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023126250
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0013】 本願によれば、正負極間の短絡を防止できると共に、負荷特性に優れた扁平形非水電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022035000001_ABST
    Figure 2025022035000001_ABST
Patent Text Reader

Abstract

To provide a flat nonaqueous battery having high reliability and load characteristics.SOLUTION: A flat nonaqueous battery includes a positive electrode, a negative electrode, a separator, and a nonaqueous electrolytic solution. The negative electrode includes a lithium layer and a Li-Al alloy layer formed on one surface of the lithium layer. The Li-Al alloy layer and the separator are in contact with each other. The separator is composed of fabric or nonwoven fabric of polyolefin resin. A portion of the separator located between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode. A thickness of a portion located between the positive electrode and the negative electrode of the separator is 70 to 150 μm and weight of the separator is 30 to 45 g / m2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a flat nonaqueous battery capable of preventing short circuits between positive and negative electrodes and having excellent load characteristics, and a method for manufacturing the same. [Background technology]

[0002] Flat nonaqueous batteries, which combine a positive electrode made of a compact (pellet) of a positive electrode mixture with a negative electrode made of Li metal, are used for various purposes, taking advantage of their characteristics such as high capacity and high voltage. In particular, in recent years, the demand for flat nonaqueous batteries as a power source for in-vehicle devices has been increasing.

[0003] Patent Document 1 proposes a flat nonaqueous battery in which a nonwoven fabric of aramid fibers having a thickness of about 0.05 mm to 1 mm before compression is compressed to a thickness of 50% or more and 95% or less and used as a separator for use as a power source for devices that are subjected to large centrifugal forces and vibrations, such as a tire puncture sensor for a vehicle.

[0004] However, since aramid fiber nonwoven fabric is poor in processability, it is difficult to cut it to a predetermined size and compress it.

[0005] On the other hand, in flat nonaqueous batteries, a Li-Al alloy layer may be formed on the separator-side surface of the Li metal of the negative electrode in order to improve load characteristics, etc. By alloying the surface of the Li metal layer with Al, the crystal grains of the alloy layer on the surface of the negative electrode are refined and fine irregularities are formed on the surface of the alloy layer (hereinafter, also simply referred to as "refinement of the negative electrode surface"). This increases the reaction area of ​​the negative electrode and improves the load characteristics.

[0006] However, since the irregularities formed on the surface of the alloy layer of the negative electrode are minute, when a fibrous separator such as a nonwoven fabric is used, the irregularities formed on the surface of the alloy layer of the negative electrode tend to penetrate into the pores of the separator. Furthermore, the fine crystal grains of the alloy layer may be pulverized and fall off, penetrating into the pores of the separator.

[0007] In addition, when a positive electrode made of a positive electrode mixture containing a positive electrode active material such as manganese dioxide and a conductive additive is subjected to strong vibration, the positive electrode active material, conductive additive, etc. may fall off from the positive electrode mixture and enter the pores of the fibrous separator.

[0008] For this reason, in a flat nonaqueous battery that combines a positive electrode made of a molded positive electrode mixture with a negative electrode formed by forming a Li-Al alloy layer on the surface of a Li metal layer, the positive electrode materials such as the positive electrode active material and conductive additive that have penetrated into the separator and the negative electrode materials caused by unevenness or pulverization formed on the surface of the alloy layer of the negative electrode tend to come into contact inside the separator, easily causing a short circuit. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2016-213126 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present application has been made to solve the above problems, and provides a flat nonaqueous battery that can prevent short circuits between positive and negative electrodes and has excellent load characteristics. [Means for solving the problem]

[0011] The flat nonaqueous battery of the present application includes a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte, the negative electrode includes a lithium layer and a Li-Al alloy layer formed on one surface of the lithium layer, the Li-Al alloy layer and the separator are in contact with each other, the separator is made of a woven or nonwoven fabric of a polyolefin resin, a portion of the separator located between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode, the portion of the separator located between the positive electrode and the negative electrode has a thickness of 70 to 150 μm, and the separator has a basis weight of 30 to 45 g / m. 2 It is characterized in that:

[0012] Further, a manufacturing method for a flat nonaqueous battery of the present application is a method for manufacturing the flat nonaqueous battery of the present application, characterized in that it includes a step of laminating an aluminum layer on a surface of a lithium layer to prepare a negative electrode precursor, a step of sandwiching and compressing a separator made of a woven or nonwoven fabric of a polyolefin resin between a positive electrode and the aluminum layer side of the negative electrode precursor, and a step of reacting the aluminum layer of the negative electrode precursor with Li to form a Li-Al alloy layer on the surface of the lithium layer to prepare a negative electrode. Effect of the Invention

[0013] According to the present application, it is possible to provide a flat nonaqueous battery that can prevent short circuits between positive and negative electrodes and has excellent load characteristics. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of a flat nonaqueous battery according to an embodiment. [Diagram 2] FIG. 2 is an enlarged view of part A in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] (Flat type non-aqueous battery) An embodiment of the flat nonaqueous battery of the present application will be described. The flat nonaqueous battery of this embodiment includes a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte, the negative electrode includes a lithium layer and a Li-Al alloy layer formed on one surface of the lithium layer, the Li-Al alloy layer and the separator are in contact with each other, the separator is made of a woven or nonwoven fabric of a polyolefin resin, a portion of the separator located between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode, the thickness of the portion of the separator located between the positive electrode and the negative electrode is 70 to 150 μm, and the basis weight of the separator is 30 to 45 g / m. 2 The lithium layer means a layer containing Li element, and includes a metallic lithium layer and a lithium alloy layer.

[0016] In the flat nonaqueous battery of this embodiment, the negative electrode includes a lithium layer and a Li-Al alloy layer formed on one surface of the lithium layer, and the Li-Al alloy layer is in contact with the separator. This makes it possible to refine the crystal grains of the Li-Al alloy layer on the separator-side surface of the negative electrode and to form fine irregularities on the surface of the Li-Al alloy layer, thereby increasing the reaction area of ​​the negative electrode and improving the load characteristics.

[0017] In the flat nonaqueous battery of the present embodiment, the separator is made of a woven or nonwoven fabric of a polyolefin resin, and a portion between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode. The thickness of the portion between the positive electrode and the negative electrode of the separator is 70 to 150 μm, and the basis weight of the separator is 30 to 45 g / m. 2 Since the thickness of the separator is set to 100 μm, the pores of the separator are made fine, and the negative electrode material from the negative electrode and the positive electrode material from the positive electrode are less likely to enter the pores of the separator, thereby preventing the negative electrode material and the positive electrode material from coming into contact with each other inside the separator and causing a short circuit.

[0018] In particular, in a positive electrode formed from a molded body of a positive electrode mixture containing a positive electrode active material such as manganese dioxide and a conductive additive, the positive electrode active material, the conductive additive, and the like are likely to fall off from the positive electrode mixture and enter the pores of the fibrous separator when subjected to strong vibration. However, even when such a positive electrode is used in the flat nonaqueous battery of this embodiment, the action of the compressed separator of this embodiment can effectively prevent a short circuit between the positive and negative electrodes.

[0019] Hereinafter, the flat nonaqueous battery of this embodiment will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view showing an example of the flat nonaqueous battery of this embodiment, and FIG. 2 is an enlarged view of part A in FIG. 1. In FIG. 1, the flat nonaqueous battery 1 has a laminated electrode body 40 and a nonaqueous electrolyte (not shown) sealed in the interior S of an exterior body composed of an exterior can 10, a sealing can 20, and a gasket 30 interposed therebetween. The laminated electrode body 40 is composed of a substantially cylindrical positive electrode 41 made of a molded body of a positive electrode mixture, a disk-shaped negative electrode 42 in which a Li-Al alloy layer 42b is formed on one surface of a lithium layer 42a, and a separator 43. The portion of the separator 43 located between the positive electrode 41 and the negative electrode 42 is compressed by the positive electrode 41 and the negative electrode 42.

[0020] The sealing can 20 is fitted into the opening of the outer can 10 via a gasket 30, and the open end of the outer can 10 is tightened inward, whereby the gasket 30 abuts against the sealing can 20, sealing the opening of the outer can 10 and forming an airtight structure for the interior S of the exterior body.

[0021] The exterior can 10 has a circular bottom portion 11 and a cylindrical peripheral wall portion 12 formed on the outer periphery of the bottom portion 11 in a continuous manner. A mesh member 51 is joined to the inner bottom surface of the bottom portion 11. When the battery is assembled, the mesh member 51 is pressed so as to bite into the positive electrode mixture of the positive electrode 41. The mesh member 51 can strengthen the electrical contact between the exterior can 10 and the positive electrode 41.

[0022] The sealing can 20 has a circular flat portion 21 and a cylindrical peripheral wall portion 22 formed on the outer periphery of the flat portion 21 in a continuous manner with the flat portion 21. The peripheral wall portion 22 has a base end portion 22a located on the flat portion 21 side, a step portion 22c extending radially outward from the base end portion 22a, and an expanded diameter portion 22b having a larger diameter than the base end portion 22a. That is, the peripheral wall portion 22 has a step portion 22c formed between the base end portion 22a and the expanded diameter portion 22b, which connects the two.

[0023] The gasket 30 is disposed so as to be sandwiched between the open end of the peripheral wall portion 22 of the sealing can 20 and the bottom surface portion 11 of the outer can 10. Specifically, the gasket 30 includes a ring-shaped base portion 31, an outer cylinder wall 32 protruding from the outer peripheral edge of the base portion 31, and an inner cylinder wall 33 extending from the inner peripheral edge of the base portion 31 in the same direction as the outer cylinder wall 32.

[0024] Next, each of the components of the flat nonaqueous battery of this embodiment will be described.

[0025] <Negative electrode> 1 and 2, the negative electrode 42 of this embodiment includes a lithium layer 42a and a Li-Al alloy layer 42b formed on one surface of the lithium layer 42a, and the Li-Al alloy layer 42b is in contact with the separator 43. This makes the crystal grains of the Li-Al alloy layer finer and forms fine irregularities on the surface of the Li-Al alloy layer, thereby increasing the reaction area of ​​the negative electrode and improving the load characteristics.

[0026] In order to sufficiently advance the refinement of the negative electrode surface and improve the load characteristics of the negative electrode, the content of Al contained in the Li-Al alloy layer is preferably 5% or more, more preferably 6% or more, in terms of mass ratio, based on the total amount of Li and Al in the Li-Al alloy layer. On the other hand, if the refinement of the negative electrode surface advances too much, the refined Li-Al alloy is likely to penetrate to a position close to the positive electrode in the separator, which makes it easier to cause a short circuit, so the content of Al contained in the Li-Al alloy layer is preferably 12% or less, more preferably 10% or less, in terms of mass ratio, based on the total amount of Li and Al in the Li-Al alloy layer.

[0027] The lithium layer 42a can be made of metallic lithium or a lithium alloy processed into a disk shape. The metallic lithium used for the lithium layer 42a may contain unavoidable impurities. Examples of alloy components contained in the lithium alloy include elements such as Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, Mo, Sn, and Si. The content of the elements that are alloy components of the lithium alloy is usually 10 mass % or less.

[0028] The negative electrode 42 can be obtained, for example, by laminating aluminum foil on a lithium plate of a certain shape and thickness to form a negative electrode precursor, using the negative electrode precursor as is to assemble a battery, and after assembly, electrochemically reacting the lithium plate and the aluminum foil to form a Li-Al alloy, and forming a Li-Al alloy layer 42b on one surface of the lithium layer 42a.

[0029] In the negative electrode 42, the thickness of the lithium layer 42a is not particularly limited, but may be 100 to 500 μm depending on the battery capacity. The thickness of the Li-Al alloy layer 42b is also not particularly limited, but if it is too thick, the strength of the negative electrode 42 decreases, so that it is usually 1 to 7% of the thickness of the lithium layer 42a.

[0030] Examples of the aluminum foil used in the negative electrode precursor include a foil made of Al (and unavoidable impurities) and a foil made of an Al alloy containing alloy components such as Cu, Fe, Ni, Co, Mn, Cr, V, Ti, Zr, Nb, and Mo, with the balance being Al and unavoidable impurities (the content of the alloy components is, for example, 10 mass% or less in total).

[0031] The lithium layer 42a and the Li-Al alloy layer 42b of the negative electrode 42 shown in FIGS. 1 and 2 can be distinguished by observing a cross section of the negative electrode 42 with a scanning electron microscope (SEM).

[0032] <Positive electrode> The positive electrode 41 of this embodiment can be, for example, a molded body obtained by pressure molding a positive electrode mixture containing a positive electrode active material, a conductive assistant, a binder, and the like into a pellet shape.

[0033] The positive electrode active material is preferably a manganese oxide or a lithium manganese composite oxide. The manganese oxide is particularly preferably manganese dioxide. The lithium manganese composite oxide is preferably an oxide having a spinel structure such as LiMn2O4, an oxide having a layered structure such as Li2MnO3 or LiMnO2, an oxide in which Li is inserted into manganese dioxide, or an oxide having low crystallinity that can be synthesized at a relatively low temperature and has a composition such as LiMn3O6. Graphite fluoride may also be used as the positive electrode active material.

[0034] Examples of the conductive assistant that can be used include carbon materials such as carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon fibers; conductive fibers, such as metal fibers; carbon fluoride; metal powders, such as copper and nickel; and organic conductive materials, such as polyphenylene derivatives.

[0035] Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), and polyvinylpyrrolidone (PVP).

[0036] The positive electrode mixture preferably contains, for example, 80 to 96% by mass of positive electrode active material, 2 to 10% by mass of conductive additive, and 2 to 10% by mass of binder. The thickness of the molded body made of the positive electrode mixture is preferably 500 to 900 μm.

[0037] <separator> The separator 43 of this embodiment is made of, for example, a woven or nonwoven fabric made of polyolefin such as polyethylene (PE) or polypropylene (PP), and the portion of the separator 43 located between the positive electrode 41 and the negative electrode 42 is compressed by the positive electrode 41 and the negative electrode 42. In addition, in FIG. 2, the thickness X of the portion of the separator 43 located between the positive electrode 41 and the negative electrode 42 is set to 70 to 150 μm, and the thickness Y of the portion of the separator 43 not located between the positive electrode 41 and the negative electrode 42 is set to 200 to 400 μm. That is, a part of the separator 43 is not sandwiched between the positive electrode 41 and the negative electrode 42, and extends outward from the laminated electrode body 40. Furthermore, the basis weight of the separator 43 is 30 to 45 g / m 2 is set to.

[0038] The thickness X of the portion of the separator 43 located between the positive electrode 41 and the negative electrode 42 is 70 μm or more, preferably 80 μm or more, after being compressed and reduced by the positive electrode and the negative electrode, in order to prevent the positive electrode and the negative electrode from being too close to each other and thus prone to short-circuiting. In addition, the thickness of the separator after being reduced is 150 μm or less, preferably 120 μm or less, in order to prevent the separator from being short-circuited by compressing the separator to a certain thickness or less and pressing the fibers together to eliminate coarse pores.

[0039] The thickness of the separator 43 can be measured by a digital thickness gauge equipped with a measuring pin having a flat surface with a diameter of 6.5 mm.

[0040] The weight of the separator 43 is set to 30 g / m2 in order to prevent short circuits by making the amount of the separator fiber more than a certain amount. 2 More than 32g / m 2 On the other hand, if the amount of fibers in the separator is too large, the separator becomes difficult to compress and there is a risk of the load characteristics of the battery decreasing. Therefore, the basis weight of the separator is preferably 45 g / m 2 Less than 40g / m 2 The following is preferred:

[0041] The thickness of the separator 43 after compression at the portion located between the positive electrode and the negative electrode is preferably 30% or more, more preferably 40% or more, and more preferably 70% or less, more preferably 60% or less of the thickness before compression. This is because if the change in thickness due to compression is too large, problems such as the thickness after compression being likely to vary and the sealing property being likely to vary will occur. Also, if the change in thickness due to compression is too small, the pressure applied to the separator from the positive electrode and the negative electrode will be small, and the separator may be displaced due to vibration or the like.

[0042] In addition, the separator 43 is preferably formed by bonding two or more layers of nonwoven fabric together. This increases the probability that the continuity of the through-holes will be interrupted at the interface between the multiple layers of nonwoven fabric, even if fine through-holes exist in the nonwoven fabric, and therefore more reliably prevents the positive electrode material that has fallen off the positive electrode 41 and the pulverized negative electrode material from penetrating through the separator 43 and coming into contact with each other to cause a short circuit. In this case, the separator 43 may be formed by laminating multiple nonwoven fabrics of the same material, or may be formed by laminating nonwoven fabrics of different materials one by one.

[0043] <Nonaqueous electrolyte> The non-aqueous electrolyte used is a solution in which a lithium salt is dissolved in an organic solvent.

[0044] Examples of organic solvents for non-aqueous electrolytes include cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; chain esters such as methyl propionate; cyclic esters such as compounds having lactone rings; chain ethers such as 1,2-dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme; cyclic ethers such as dioxane, tetrahydrofuran, and 2-methyltetrahydrofuran; nitriles such as acetonitrile, propionitrile, and methoxypropionitrile; sulfites such as ethylene glycol sulfite; and the like, and these can be used in combination of two or more. In order to obtain a battery with better characteristics, it is desirable to use a combination that can obtain high conductivity, such as a mixed solvent of a cyclic carbonate and a chain ether.

[0045] Examples of lithium salts for the non-aqueous electrolyte include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, LiCF3CO2, Li2C2F4(SO3)2, LiN(CF3SO2)2, LiC(CF3SO2)3, LiC n F 2n+1 SO3 (2≦n≦7), LiN(RfOSO2)2 (where Rf is a fluoroalkyl group), etc.

[0046] The concentration of the lithium salt in the nonaqueous electrolyte is preferably 0.3 mol / L or more and 1.2 mol / L or less.

[0047] <Exterior body> The materials that can be used for the outer can 10 and the sealing can 20 that constitute the outer casing include, for example, carbon steel and stainless steel. The mesh member 51 joined to the inner bottom surface of the bottom portion 11 of the outer can 10 can be made of a metal such as nickel, aluminum, stainless steel, etc., and can be joined to the inner bottom surface of the bottom portion 11 of the outer can 10 by spot welding or the like. The material that can be used for the gasket 30 includes, for example, polypropylene, polyphenylene sulfide, and perfluoroalkoxyethylene.

[0048] The flat nonaqueous battery 1 of this embodiment is coin-shaped, but is not limited to a coin shape and may be thin and rectangular.

[0049] (Manufacturing method of flat non-aqueous battery) Next, an embodiment of a method for manufacturing a flat nonaqueous battery of the present application will be described. The method for manufacturing a flat nonaqueous battery of the present application is a method for manufacturing the flat nonaqueous battery of the present application described above, and includes a step of laminating an aluminum layer on the surface of a lithium layer to prepare a negative electrode precursor, a step of sandwiching and compressing a separator made of a woven or nonwoven fabric of a polyolefin resin between a positive electrode and the aluminum layer side of the negative electrode precursor, and a step of reacting the aluminum layer of the negative electrode precursor with Li to form a Li-Al alloy layer on the surface of the lithium layer to prepare a negative electrode.

[0050] In the reaction between the aluminum layer of the negative electrode precursor and Li, after assembling the battery, the lithium layer of the negative electrode precursor and the aluminum layer are electrochemically reacted to form a Li-Al alloy, and a Li-Al alloy layer can be formed on one surface of the lithium layer. This makes the crystal grains of the Li-Al alloy layer on the separator side surface of the negative electrode finer, and forms fine irregularities on the surface of the Li-Al alloy layer, thereby increasing the reaction area of ​​the negative electrode and enabling the manufacture of a flat nonaqueous battery with excellent load characteristics.

[0051] Furthermore, according to the manufacturing method for a flat nonaqueous battery of the present embodiment, a portion of the separator located between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode, thereby making the pores of the separator finer and making it difficult for the negative electrode material from the negative electrode or the positive electrode material from the positive electrode to enter the pores of the separator. As a result, a flat nonaqueous battery can be manufactured in which the negative electrode material and the positive electrode material can be prevented from coming into contact with each other inside the separator and causing a short circuit.

[0052] The separator before compression used in the method for producing a flat nonaqueous battery of this embodiment is a woven or nonwoven polyolefin resin fabric having a thickness of, for example, 200 μm or more, preferably 250 μm or more and 400 μm or less, preferably 350 μm or less.

[0053] The separator is sandwiched between the positive electrode and the Al layer side of the negative electrode precursor and compressed in the sealing step in the assembly of the battery to a thickness of 70 to 150 μm or less, preferably 80 to 120 μm. In this case, the separator having a thickness of 200 to 400 μm may be compressed as is, but in this case, the thickness needs to be significantly reduced and there is a risk of variation in the thickness after compression, so it is preferable to compress the separator to a certain extent beforehand prior to the assembly of the battery, and use the compressed separator in the assembly of the battery.

[0054] The thickness of the compressed separator is preferably 55 to 75% of the thickness before the compression processing, more preferably 60% or more of the original thickness, and more preferably 70% or less of the original thickness.

[0055] In the step of compressing the separator by sandwiching it between the positive electrode and the Al layer side of the negative electrode precursor, if the change in thickness of the separator due to compression is too large, problems such as the separator being more likely to have variation in thickness after compression, or more likely to have variation in sealing performance, etc. Also, if the change in thickness of the separator due to compression is too small in the step of compressing the separator, the pressing force that the separator receives from the positive electrode and negative electrode becomes small, and the separator may become displaced due to vibration or the like.

[0056] For this reason, in assembling a battery, the thickness of the separator after compression at the portion located between the positive electrode and the negative electrode is preferably 30% or more, more preferably 40% or more, of the thickness before compression (in the case of a separator that has been compressed in advance, the thickness after the processing), and is preferably 70% or less, and more preferably 60% or less. EXAMPLES

[0057] The present application will be described in detail below based on examples, but the following examples are not intended to limit the present application.

[0058] Example 1 <Compression processing of separator> Two layers of polypropylene nonwoven fabric are bonded together to form a sheet with a thickness of 300 μm and a basis weight of 35 g / m. 2 The separator was calendered and compressed to a thickness of 200 μm.

[0059] Next, in order to reproduce the situation in which powder falls off from the positive electrode, a certain amount of manganese dioxide powder was evenly sprinkled onto one side of the compressed separator.

[0060] <Preparation of positive electrode> A positive electrode mixture was prepared by mixing manganese dioxide, which is a positive electrode active material, carbon black, which is a conductive additive, and PTFE, which is a binder, in a mass ratio of 90:5:5. The positive electrode mixture was then pressure-molded to produce a disk-shaped positive electrode, which was 16 mm in diameter and 1.8 mm thick and was composed of a molded body of the positive electrode mixture.

[0061] <Preparation of negative electrode forming member> A piece of metallic lithium was placed on the inner bottom surface of a circular stainless steel sealed can and shaped to be circular in plan view, forming a lithium layer with a diameter of 16 mm and a thickness of 1.2 mm. Furthermore, an aluminum foil with a thickness of 9 μm was laminated on top of the lithium layer to produce a laminate of a lithium layer and an aluminum layer (anode forming member) for forming the anode.

[0062] <Preparation of non-aqueous electrolyte> Propylene carbonate, 1,2-dimethoxyethane, and LiClO4 were mixed in a mass ratio of 55:40:5 to prepare a nonaqueous electrolyte solution containing LiClO4 at a concentration of 0.5 mol / L.

[0063] <Battery assembly> A gasket was attached to a sealing can having a laminate of a lithium layer and an aluminum layer formed on the inner bottom surface, and the separator and the positive electrode were placed in that order on top of the aluminum layer of the laminate, with the side of the separator from which the manganese dioxide powder had been shaken off facing the positive electrode.

[0064] Next, the nonaqueous electrolyte was dropped into the sealed can, and then a stainless steel outer can having a circular punched nickel mesh spot-welded to its inner bottom surface was placed on top of the can. While pressing the outer can against the can so as to compress the separator, the open end of the outer can was tightened inwardly and a gasket was brought into contact with the sealed can to seal the opening of the outer can, thereby assembling a flat nonaqueous battery.

[0065] After the battery was assembled, the aluminum layer of the laminate of the lithium layer and the aluminum layer reacted with lithium to form an alloy, thereby obtaining a lithium negative electrode in which a Li-Al alloy layer was formed on the surface of the lithium layer.

[0066] In addition, the thickness of the separator located between the positive and negative electrodes was compressed to 100 μm during battery assembly, which was 50% of the thickness (200 μm) of the separator before battery assembly.

[0067] Comparative Example 1 Two layers of polypropylene nonwoven fabric are bonded together to form a sheet with a thickness of 300 μm and a basis weight of 35 g / m. 2 The separator was not calendered, and manganese dioxide powder was evenly sprinkled onto one side of the uncompressed separator in the same manner as in Example 1. A flat nonaqueous battery was assembled in the same manner as in Example 1, except that this separator was used for assembling the battery.

[0068] The thickness of the separator located between the positive and negative electrodes was compressed to 200 μm during battery assembly, which was 67% of the thickness (300 μm) of the separator before battery assembly.

[0069] Comparative Example 2 Two layers of polypropylene nonwoven fabric are bonded together to form a sheet with a thickness of 300 μm and a basis weight of 35 g / m. 2 The separator was calendered, compressed to a thickness of 100 μm, and then the manganese dioxide powder was evenly shaken off in the same manner as in Example 1. Except for this, a flat nonaqueous battery was assembled in the same manner as in Example 1.

[0070] The thickness of the separator located between the positive and negative electrodes was compressed to 50 μm during battery assembly, which was 50% of the thickness (100 μm) of the separator before battery assembly.

[0071] Comparative Example 3 Weight: 25g / m 2 A flat nonaqueous battery was assembled in the same manner as in Example 1, except that the separator was used.

[0072] The thickness of the separator located between the positive and negative electrodes was compressed to 100 μm during battery assembly, which was 50% of the thickness (200 μm) of the separator before battery assembly.

[0073] Comparative Example 4 Weight: 50g / m 2 A flat nonaqueous battery was assembled in the same manner as in Example 1, except that the separator was used.

[0074] The thickness of the separator located between the positive and negative electrodes was compressed to 100 μm during battery assembly, which was 50% of the thickness (200 μm) of the separator before battery assembly.

[0075] Comparative Example 5 A lithium layer having a thickness of 0.35 mm was formed on the inner bottom surface of a stainless steel canister, and a flat nonaqueous battery was assembled in the same manner as in Example 1, except that no aluminum foil was laminated thereon.

[0076] The thickness of the separator located between the positive and negative electrodes was compressed to 100 μm during battery assembly, which was 50% of the thickness (200 μm) of the separator before battery assembly.

[0077] The fabricated batteries of Example 1 and Comparative Examples 1 to 5 were evaluated for reliability and load characteristics.

[0078] <Reliability evaluation> The open circuit voltage (OCV) was measured for 10 batteries from each of the Examples and Comparative Examples. Batteries with a voltage of 3.1 V or less were determined to be short-circuited batteries, and the reliability of the batteries was evaluated based on the number of such batteries.

[0079] <Evaluation of load characteristics> The batteries of Example 1, Comparative Example 2, and Comparative Examples 4 and 5, which did not suffer from short-circuiting in the reliability evaluation, were discharged at room temperature equivalent to an electrical charge of 120 mAh, and then held in a thermostatic chamber at -40° C. After the temperature of the batteries had dropped, they were discharged at a current value of 10 mA, and the discharge voltage (CCV) of the batteries 10 ms after the start of discharge was measured to evaluate the load characteristics at low temperatures.

[0080] The above evaluation results are shown in Table 1 together with the separator configuration of each battery.

[0081] [Table 1]

[0082] Among the batteries of Example 1 and Comparative Examples 1 to 4 in which a Li-Al alloy layer was formed on the surface of the lithium layer of the negative electrode, in the battery of Example 1, the separator located between the positive electrode and the negative electrode was compressed to a thickness of 70 to 150 μm, and the weight of the separator was 30 to 45 g / m 2As a result, it was possible to suppress the occurrence of short circuits, resulting in a battery with excellent load characteristics.

[0083] On the other hand, the battery of Comparative Example 1 had a short circuit due to insufficient compression of the separator, the battery of Comparative Example 2 had a deteriorated load characteristic due to excessive compression of the separator, the battery of Comparative Example 3 had a short circuit due to an excessively small separator basis weight, and the battery of Comparative Example 4 had a deteriorated load characteristic due to an excessively large separator basis weight. Also, the battery of Comparative Example 5 had a deteriorated load characteristic due to the absence of a Li-Al alloy layer on the surface of the lithium layer of the negative electrode. [Industrial Applicability]

[0084] The flat nonaqueous battery of the present application has high reliability and load characteristics, and by taking advantage of these characteristics, the battery can be preferably applied to applications requiring good capacity maintenance over a long period of time, such as power sources for in-vehicle devices and outdoor equipment. [Explanation of symbols]

[0085] 1 Flat nonaqueous battery 10 Outer can 11 Bottom part 12 Peripheral wall section 20 Sealed cans 21 Plane part 22 Peripheral wall section 30 Gasket 31 Base 32 Outer cylinder wall 33 Inner cylinder wall 40 Laminated electrode body 41 Positive electrode 42 Negative electrode 43 Separator 51 Net components

Claims

1. A flat non-aqueous battery including a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, The negative electrode includes a lithium layer and a Li-Al alloy layer formed on one surface of the lithium layer, the Li-Al alloy layer and the separator are in contact with each other; The separator is made of a woven or nonwoven fabric of a polyolefin resin, a portion of the separator located between the positive electrode and the negative electrode is compressed by the positive electrode and the negative electrode, The thickness of the separator at a portion located between the positive electrode and the negative electrode is 70 to 150 μm, The separator has a basis weight of 30 to 45 g / m 2 A flat nonaqueous battery comprising:

2. 2 . The flat nonaqueous battery according to claim 1 , wherein the thickness of the separator after compression at a portion located between the positive electrode and the negative electrode is 30% or more of the thickness before compression.

3. 2 . The flat nonaqueous battery according to claim 1 , wherein the thickness of the separator after compression at a portion located between the positive electrode and the negative electrode is 70% or less of the thickness before compression.

4. 2. The flat nonaqueous battery according to claim 1, wherein the separator has a thickness of 200 to 400 μm at a portion not located between the positive electrode and the negative electrode.

5. 2. The flat nonaqueous battery according to claim 1, wherein the separator is formed by laminating two or more layers of nonwoven fabric.

6. The flat nonaqueous battery according to claim 1 , wherein the positive electrode includes a molded body of a positive electrode mixture.

7. 2. The flat nonaqueous battery according to claim 1, wherein the content of Al contained in the Li-Al alloy layer of the negative electrode is 5 to 12% by mass of the total amount of Li and Al in the Li-Al alloy layer.

8. A method for producing the flat nonaqueous battery according to any one of claims 1 to 7, comprising the steps of: forming a negative electrode precursor by laminating an aluminum layer on a surface of the lithium layer; A method for producing a flat non-aqueous battery, comprising: a step of sandwiching and compressing a separator made of a woven or non-woven fabric of a polyolefin resin between a positive electrode and the aluminum layer side of the negative electrode precursor; and a step of reacting the aluminum layer of the negative electrode precursor with Li to form a Li-Al alloy layer on a surface of the lithium layer, thereby producing a negative electrode.

9. The method for producing a flat nonaqueous battery according to claim 8 , wherein the separator is a separator that has been compressed in advance.

10. 10. The method for producing a flat nonaqueous battery according to claim 9, wherein the thickness of the compressed separator is 55 to 75% of the thickness before the compression.

Citation Information

Patent Citations

  • Flat-shaped battery, manufacturing method thereof, and tire puncture detector

    JP2016213126A